The Effects of an Eight Week Weight Loss Program in Obese Adults Utilizing a Nutritional Supplement - Lane, Gerry (Journal of Nutritional Therapeutics, 2016)
A non-placebo controlled, blinded study utilizing a commercially available meal replacement (manufactured by Nutrition Laboratories Inc., Florida) studied 35 adult participants to determine the safety and efficacy of the product (a liquid nutrient concentrate) while measuring weight reduction, lipids, and adipose tissue, liver enzymes and metabolic indices (glucose, cholesterol and triglycerides) over an eight-week period. The average weight loss after 14 days was 18.2 (± 3.7) pounds and 28.4 (± 6.5) pounds at the conclusion of the eight-week trial. This was found to be statistically significant (p<.01). Patient’s metabolic functions were closely monitored in order to document therapeutic benefit, while monitoring for potential side effects. Total cholesterol was lowered in all participants (ave. reduction = 20.6 mg/dL) and every participant with clinically elevated cholesterol (≥ 200) at baseline, reported normal values after eight-weeks. Similarly, all participants with fasting hyperglycemia (s. glu. ≥ 100) returned to normal by the end of the study. This included three patients with NIDDM who were not well controlled prior to the study. There was no evidence of hypoglycemia (s. glu. ≤ 65). Participants with elevated liver enzymes at baseline reported normal SGOT & SGPT levels after two-weeks. No participant developed liver enzyme elevations. Subjective energy level of the participants was reported at baseline as low to average and reported as high to very high at the conclusion of the study. All participants lost total adipose tissue with the average change calculated at a 6.7% loss.